Nanohybrids with Magnetic and Persistent Luminescence Properties for Cell Labeling, Tracking, In Vivo Real‐Time Imaging, and Magnetic Vectorization. Issue 16 (15th March 2018) - Teston, Eliott; Maldiney, Thomas; Marangon, Iris; Volatron, Jeanne; Lalatonne, Yoann; Motte, Laurence; Boisson‐Vidal, Catherine; Autret, Gwennhael; Clément, Olivier; Scherman, Daniel; Gazeau, Florence; Richard, Cyrille
Abstract: Once injected into a living organism, cells diffuse or migrate around the initial injection point and become impossible to be visualized and tracked in vivo. The present work concerns the development of a new technique for therapeutic cell labeling and subsequent in vivo visualization and magnetic retention. It is hypothesized and subsequently demonstrated that nanohybrids made of persistent luminescence nanoparticles and ultrasmall superparamagnetic iron oxide nanoparticles incorporated into a silica matrix can be used as an effective nanoplatform to label therapeutic cells in a nontoxic way in order to dynamically track them in real‐time in vitro and in living mice. As a proof‐of‐concept, it is shown that once injected, these labeled cells can be visualized and attracted in vivo using a magnet. This first step suggests that these nanohybrids represent efficient multifunctional nanoprobes for further imaging guided cell therapies development. Abstract : Nanohybrids made of persistent luminescence nanoparticles (PLNPs) and ultrasmall superparamagnetic iron oxide nanoparticles (USPIO) incorporated into a silica matrix can be used as an effective nanoplatform to label therapeutic cells in a nontoxic way in order to dynamically track them in real‐time in vitro and in living mice.